Novo sistema de aplicação de drogas em cirurgias oftalmológicas - Pinheiro, Francisco Irochima (2011)
The topical corneal application of antimitotic mitomycin-C (MMC) during refractive surgery is still characterized by a lack of standardization and considerable empirism. For this reason the creation of a system capable of reliable drug delivery represents a beneficial innovation for patients submitted to these procedures. Objective: Elaborate a new MMC delivery system during the transoperatory period of photorefractive keratectomy (PRK) followed by patent application. Methods: The project consists of an in vitro experimental study to create an MMC (0.02%) release system. The drug was impregnated in sterile Whatman® 41 paper filter discs with a diameter of 8 mm. After drying, the discs were applied to antibiogram plates seeded with Staphylococcus epidermidis (American Type Culture Collection ATCC 12228), followed by the addition of a drop of sterile water. At the end of 1 minute, the discs were removed and the plates incubated for 48 hours at 35oC. Mean drop volume in the collyrium flasks was measured using analytical balance weighing. The inhibition halo (mm) was correlated with the MMC impregnated into the disc. After completion of the invention design a patent application was lodged at the National Institute of Industrial Property. Results: The correspondence between MMC-produced inhibition halos indicated that a dose of 16μg was ideal for impregnating into the discs. The mean drop volume obtained from the collyrium flasks was 37.7 μL. A minute after the application of one drop of balanced saline solution, the system released an adequate concentration for PRK surgery. Conclusion: A new MMC delivery system was created for transoperatory application in photorefractive keratectomy (PRK). Publication of the patent application (number PI 0704739-8) gives the authors exclusive intellectual property rights. The study was sponsored by Ophthalmos Indústria e Comércio de Produtos Farmacêuticos S.A. (São Paulo-SP, Brazil) and received the indispensable scientific contribution of researchers from the fields of Pharmacy, Medicine, Biology, Statistics and Law, characterizing the work as multidisciplinary, in accordance with norms established by the Postgraduate Health Sciences Program of the Federal University of Rio Grande do Norte (UFRN)